[PP.36.24]: ASSESSMENT OF THE TREATMENT OF ANTICOAGULANT IN PATIENTS DIAGNOSED ATRIAL FIBRILLATION. (June 2015) - Aguilera>, B.M.>; Cordovilla, A.M.; Conesa, M.J.; Mroz, J.; Sánchez, C.; Ariza, C.; García, Z.M.; Menarguez, F.H.; Leal, M.; Abellán, J.
Abstract : Objective: To determine whether there is an adequate indication of anticoagulant therapy and to assess the risk of bleeding. Design and method: This observational, descriptive, longitudinal, prospective study of patients with atrial fibrillation episode recorded in patient history. Analytical analysis were collected (control of INR) demographic variables (age, sex), clinical (blood pressure, type and character of the FA, CHA2DS2 - VASc scale, HAS- BLED scale, treatment) and analytical (INR control). Results: 66.1 % of patients with high thromboembolic risk are anticoagulated with drugs antivitamin K (AVK). Patients who are at low risk with 11.8% antiplatelet therapy. Even in 48.3% of patients with low risk they are not prescribed antiplatelet or anticoagulant therapy. 89.9% of patients with high thromboembolic risk are at low risk of bleeding. Among patients with low thromboembolic risk there are none which present a high risk of bleeding. 78% of patients with high thromboembolic risk are anticoagulated versus 76.5 % low risk are not. Of these, there is a 73.8% of patients who are anticoagulated, there are 11.1% compared with 15.1 % antiplatelet agents in the treatment it is not prescribed. Regarding the risk of bleeding, most patients (74.9 %) presented a score < 3 in the HAS- BLEED scale and 7.7 % respresented a high bleeding risk based on this. Conclusions: Adequate anticoagulation is confirmed according to CHA2DS2 VASc HAS- BLED and scales. 23.5% of patients at low risk of revision anticoagulated subsidiary of antithrombotic therapy is detected.